2015
DOI: 10.1158/0008-5472.can-14-3297
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Induced TMPRSS2 Activates Matriptase and Promotes Extracellular Matrix Degradation, Prostate Cancer Cell Invasion, Tumor Growth, and Metastasis

Abstract: Dysregulation of androgen signaling and pericellular proteolysis is necessary for prostate cancer progression, but the links between them are still obscure. In this study, we show how the membrane-anchored serine protease TMPRSS2 stimulates a proteolytic cascade that mediates androgen-induced prostate cancer cell invasion, tumor growth, and metastasis. We found that matriptase serves as a substrate for TMPRSS2 in mediating this proinvasive action of androgens in prostate cancer. Further, we determined that hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 46 publications
1
142
0
1
Order By: Relevance
“…Reminiscent of the role of TGFβ in cancer and metastatic progression, NID1 seems to be a tumor suppressor and metastasis promoter in our breast cancer and melanoma models. However, these functions may be cancer type-dependent, as NID1 promoted tumorigenesis and metastasis of endometrial cancer (Pedrola et al 2015), while loss of expression through promoter methylation in colon and gastric cancers (Ulazzi et al 2007) or increased protein degradation in prostate cancer (Ko et al 2015) correlated with enhanced tumor growth and metastasis. One possible mechanism by which NID1 may decrease tumorigenesis could be its strong binding affinity for perlecan, which can be secreted by quiescent ECs to mute proliferative and invasive phenotypes of lung and breast cancer cells in vitro and reduce their protumorigenic and proinflammatory signaling (Franses et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reminiscent of the role of TGFβ in cancer and metastatic progression, NID1 seems to be a tumor suppressor and metastasis promoter in our breast cancer and melanoma models. However, these functions may be cancer type-dependent, as NID1 promoted tumorigenesis and metastasis of endometrial cancer (Pedrola et al 2015), while loss of expression through promoter methylation in colon and gastric cancers (Ulazzi et al 2007) or increased protein degradation in prostate cancer (Ko et al 2015) correlated with enhanced tumor growth and metastasis. One possible mechanism by which NID1 may decrease tumorigenesis could be its strong binding affinity for perlecan, which can be secreted by quiescent ECs to mute proliferative and invasive phenotypes of lung and breast cancer cells in vitro and reduce their protumorigenic and proinflammatory signaling (Franses et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Prominent TTSPs involved in PCa progression include matriptase‐1, matriptase‐2 and hepsin. Matriptase‐1 overexpression correlates with Gleason score (Riddick et al, 2005) promoting cell invasion, metastasis and prostate tumour growth (Sanders et al, 2006; Ko et al, 2015) by regulating MET signalling in PCa. Interestingly, matriptase‐1 interacts with a close relative of TMEFF2, TMEFF1, where the EGF‐like domain of TMEFF1 binds to the matriptase‐1 CUB domain (Ge et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…TTSP-regulated proteolysis is a prerequisite for tissue homeostasis, however, uncontrolled expression and enhanced enzymatic activity of cell surface-attached TTSPs can lead to different disorders such as carcinogenesis 9 and contributes to influenza and other respiratory viral infections 10 . Moreover, TMPRSS2 accumulated in the glandular lumen of normal and cancerous prostate tissues can be proteolytically cleaved and the rise in released protease fragment levels can confirm the presence of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…By use of the PAR-2 antagonist Phe-Ser-Leu-Leu-Arg-Tyr-NH 2 it was found that matriptase and TMPRSS2 can activate PAR2, which suggests an additional link between a membrane-anchored serine protease and prostate tumor metastasis. However, further studies should be conducted if excessive amount of TMPRSS2 in intracellular space may play a functional role in prostate tumorigenesis in addition to cell surface protease activity 9,13,19 .…”
Section: Introductionmentioning
confidence: 99%